NEW DIDACTIC MEANS СREATION OF A MEDICAL HIGHER SCHOOL TEACHER AS FACTOR OF HIS PROFESSIONAL-PEDAGOGICAL COMPETENCIES DEVELOPMENT - O. M. Kolomiets; N. A. Makatsariya; I. V. Khamani (IRBIS LLC, 2016)
The article considers the problem of professional-pedagogical competencies development of the Higher Medical School teacher. It is revealed dependence of improving quality of students' professional training from the level of the teacher's psychological-pedagogical and methodical competence. The article describes the process of teacher's developing of the new didactic means - «Student's Study-book» and «Student's Collection of reference tables and reference cards» as the index of teacher's professional-pedagogical competencies development.